Marketing Theory and Methods in the State of the Transitional Economy: the Case of Lithuania - Pranulis, Vytautas Pranas; Melnikas, Borisas; Virvilaitė, Regina (Ekonomika, 2002)
This paper discusses the evolution of marketing thoughts. theories and practical adaptation in countries undergoing turbulent transition. Every country undergoes certain kinds of changes and flow from one condition to another. However, not every change is defined as transition. In this paper we investigate the changes in the economic and social environment of Lithuania and other Baltic states that are defined as transitional. Through this survey we aim to show that comprehension and adoption of marketing is a specific expression of transitional changes in Lithuania. The survey covers three major questions: the comprehension of the transitional context, the comprehension of marketing as a business management theory, and marketing in the business practice of a transitional country.